Sustainability Leadership Development Among Students in Higher Education: Evidence From Ukraine - Sobolieva, Tetiana; Banit, Olga; De León Almaraz, Sofia (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
Higher education serves as an essential platform for developing sustainability leaders; therefore, the purpose of this study is to identify the potential, gaps, and directions for strengthening sustainability leadership among students. In a survey, the attitudes of management students were investigated regarding components of sustainability leadership potential, including cognitive, learning, value-oriented, behavioural, and leadership identity, as formulated by the authors based on relevant leadership concepts. The study also focused on the peculiarities of students' perceptions of sustainable development priorities in a country at war. The results indicate greater awareness and a greater willingness to learn more about sustainability among master’s students, recognition of the high importance of a sustainable approach to management, but also significant concern about the realism of its implementation. A high intentional component positively impacts the sustainability leadership position. The phenomenon of a more active stance on the role of a sustainable leader, coupled with low awareness of the sustainability concept, warrants further research. The research explores challenges in developing sustainability leaders within higher education institutions and suggests corresponding responses.